(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Abstract: The countries of the European Union, unlike the Republic of North Macedonia and the countries of Southeastern Europe, invest heavily in increasing the share of renewable energy sources in total energy production, hence becoming world leaders in the production of “clean” electricity. Therefore, the European Bank for Reconstruction and Development aims to provide support to the economy and households in the Republic of North Macedonia through loans and grants to increase the share of renewable energy sources, especially solar energy, reduce dependence on electricity imports, as well as reducing coal energy production. The Energy Strategy of the Republic of North Macedonia until 2040 defines the long-term goals for the development of individual energy activities in order to ensure security in the supply of different types of energy, while providing conditions and ways for environmental protection and measures for realization of protection. The strategy relies on green growth and offers solutions to tackle climate change, especially in the green scenario. The green scenario envisages achieving the share of renewable energy sources up to 44% in 2040 in the total final energy consumption. The role of the European Bank for Reconstruction and Development in the promotion of renewable energy sources is indisputable, as well as achieving the goals of the Energy Strategy and the green scenario, and the ultimate goal is nature protection and greater energy efficiency.